Proceedings of the 3rd International Conference on Sustainable Energy : (Vietnam VNU-HCM Publishing House, 2013)
Improve the properties of pure bio-oil aiming a direct use in diesel engines, an experimental study on the performance and emissions of diesel engine fuelled, ...